The ontogenesis of the chondrocranium and of the nasal sac of the microhylid frog Breviceps adspersus pentheri Werner - Swanepoel, J. H.(Johannes Hendrik) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1968.